Usuń nawiasy i zredukuj wyrazy podobne:
a) (3x - 4y) + (8x - 10y)
b) (12a - 36 + 10) - (4a + 5b - 2a)
c) -(4x² + 2x) - (3x - 5x² + 8)
d) (2ab - 3ab² + 4a²b) - (-5a²b + 8ab - 7ab²)
e) -3a - [-(-4ab - a - 7b) - (5a + 2ab) - 8b]

Proszę o rozwiązanie wszystkiego po kolei, a nie pisanie samych wyników.

3

Odpowiedzi

Najlepsza Odpowiedź!
2009-09-30T17:08:07+02:00
Usuń nawiasy i zredukuj wyrazy podobne:
a) (3x - 4y) + (8x - 10y)= 3x - 4y + 8x - 10y=11x 14y
b) (12a - 36 + 10) - (4a + 5b - 2a)=12a - 36 + 10 - 4a - 5b + 2a=10a-26-5b
c) -(4x² + 2x) - (3x - 5x² + 8)=-4x² - 2x - 3x + 5x² - 8=- 5x +x² - 8=
d) (2ab - 3ab² + 4a²b) - (-5a²b + 8ab - 7ab²) =
2ab - 3ab² + 4a²b +5a²b - 8ab + 7ab² = 9a²b - 6ab + 4ab²
e) -3a - [-(-4ab - a - 7b) - (5a + 2ab) - 8b]=
-3a - [+4ab + a + 7b - 5a - 2ab - 8b]= -3a -4ab - a - 7b + 5a + 2ab + 8b=
1a - 2ab +b
12 4 12
2009-09-30T17:16:47+02:00
A) (3x-4y)+8x-10y)=3x-4y+8x-10y=11x-14y
b) (12a-36+10)-(4a+5b-2a)=12a-36+10-4a-5b+2a=10a-5b-26
c) -(4x²+2x)-(3x-5x²+8)=-4x²-2x-3x+5x²-8=x²-5x-8
d)(2ab-3ab²+4a²b)-(-5a²b+8ab-7ab²)=2ab-3ab²+4a²b+5a²b-8ab+7ab²=
=-6ab+9a²b+4ab²
e) -3a-[-(-4ab-a-7b)-(5a+2ab)-8b]=-3a-[4ab+a+7b-5a-2ab-8b}=
=-3a-4ab-a-7b+5a+2ab+8b=a+b-2ab
3 4 3
2009-09-30T17:30:35+02:00
A) (3x - 4y) + (8x - 10y)= 3x-4y+8x+10y=11x+6y
b) (12a - 36 + 10) - (4a + 5b - 2a)=12a-36+10-4a-5b+2a=10a-5b-26
c) -(4x² + 2x) - (3x - 5x² + 8)=-4x²-2x-3x+5x²-8=-9x²-5x-8
d) (2ab - 3ab² + 4a²b) - (-5a²b + 8ab - 7ab²)
=2ab-3ab²+4a²b+5a²b-8ab+7ab²=-4ab+4ab²+9a²b
e) -3a - [-(-4ab - a - 7b) - (5a + 2ab) - 8b]
=-3a-[4ab+a+7b+5a-2ab+8}=-3a-4ab-a-7b-5a+2ab-8=-7a-2ab-8
3 4 3